(untitled) (Baghdad Science Journal, 2025)
Phenytoin selective electrodes were constructed based on penytoin-phosphotungstate (Ph-PT) complex with different plasticizers; di-butyl phosphate (DBP), tri-butyl phosphate (TBP), di-butyl phthalate (DBPH),and o-nitro phenyl octyl ether (NPOE) phthalate. The electrodes based on DBPH, ONPOE plasticizers gave Narnistain slope which are, 56.4 and 55.3mV/decade with detection limit of 1.9x10-5 M , 1.8x10-5 and concentration range 10-1 to 10-4 M and pH range 3.0 – 8.0. The electrodes based on TBP and DBP showed non-Nernistain slopes, 40.2,40.5 mV/decade for both plasticizers. Interfering of some cations was investigated and shows no interfering with electrodes response. Potentiometric methods were used for measuring phenytion in pharmaceutical drugs (tablets) and the electrode based on DBPH was used for determination. The recovery obtained from measuring was in good agreements with that given in British Pharmacopeias.